Correction: A phenotype of increased sleepiness in a mouse model of pulmonary hypertension and right ventricular hypertrophy. - Eric M Davis; Jeffrey J Baust; Brett J O'Donnell; Faraaz A Shah; Angela McDowell; Lanping Guo; Christopher P O'Donnell (PLoS ONE, 2019)
[This corrects the article DOI: 10.1371/journal.pone.0208540.].